The impact of the introduced Digitonthophagus gazella on a native dung beetle community in Brazil during 26 years - Filho, Walter Mesquita; Flechtmann, Carlos A. H. [UNESP]; Godoy, Wesley. A. C.; Bjornstad, Ottar N. (Springer Nature, 2018)
Following successful establishment in Australia and North America, the South African dung beetle (DB) Digitonthophagus gazella was introduced in Brazil in 1990. We investigated the impact of the exotic species on the native community of 42 native DB species using a unique weekly data set spanning 26 years, including 4 years of pre-invasion data. The invasion of D. gazella was very rapid with abundances increasing by 4 orders of magnitude during the first few years following establishment. We show that the DB diversity shrank to sixty percent of the pre-invasion level. Results from multivariate analyses identified three distinct periods of changes in composition and abundance: before the invasion (BI); after invasion I (AI-I); and AI-II each one characterized by a particular dynamic of the native species. The impacts on the native species differed according to their nesting behavior. Species with the same behavior as D. gazella (tunneler) became less abundant and five species went locally extinct. Dweller species, in contrast, became more abundant. Although the analysis of all species combined showed an increase in abundance and a less oscillatory dynamic in AI-II compared to BI, this was the case only for the dweller species, as the tunnelers showed a tendency to continued decrease throughout the 26-year study. Our results show that a new community was originated as a consequence of the invasion, in which dweller species, particularly Labarrus pseudolividus, are the dominant species and all the tunnelers, including D. gazella, are decreasing in abundance.
Keywords: Biological invasion; Dung beetles; Invasive species; Native community; Pasture area; Scarabaeidae